Efektivitas Penggunaan Rapor Digital Madrasah (RDM) Berbasis Website di MAS Al Huda Bengkalis - Natasya Humaira; Johan Andriesgo (TADRIBUNA: Journal of Islamic Education Management, 2025)
The research purpose is to analyze the effectiveness of the use of Website-based RDM as well as the supporting and inhibiting factors the effectiveness of the use of Website-based RDM at MAS Al Huda Bengkalis.The research method is qualitative research. The research results show that the use of Website-based RDM received a positive respons from informants and was considered effective in supporting the evaluation process and monitoring learning outcomes.. This is marked by the achievement of goals in accordance with the expectations and targets determined, good and fast adaptability by RDM users, the creation of job satisfaction, and the existence of a sense of full responsibility from all parties involved in the implementation of value processing activities.